Big crunch singularity: Quantization of alterity and transcendence in the light of quantum entanglement or non-locality in Maurice Blanchot's Thomas the Obscure, and When the Time Comes - Ghannaee Arani, Mohammad; Parvaneh, Farid; Chavoshian, Shohreh; Bahmanpour, Bahareh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This article is to quantize Emmanuel Levinas' manifestations of alterity and transcendence in the light of the big crunch singularity theorization, applied to the fictionality of Maurice Blanchot at a juxtaposition with the idea of the quantum entanglement or non-locality. By building its methodological foundations on the overlapping concepts of origin, image, absence, and the Other in the astrophysical and literary realms, this analytical study is to discuss how irreducible alterity of the spacetime dimensions is sustained in Blanchotian temporality of writing so as to enunciate a moment of fascination in relation with the Other and its mystery. This is where Levinas's formulation for the corrolation of time with the Other converges and anastomoses astrophysical phenomenon of quantum entanglement. How Blanchot's temporalization of writing subsists on a narrative temporality of everyday on the one hand and how it is simultaneously entangled with a diachronous extraordinary exteriority delineates where fascination reigns for Blanchot at a big crunch singularity of ethics. What Blanchot is to bring to the fore is to quantize in the space of literature such that our everyday experience of life and spacetime is definitely entangled with another unexperienced and singular spacetime whose effects on us and vice versa are not deniable.